2019
DOI: 10.1140/epjc/s10052-019-6972-4
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stability of a special class of black hole solutions in F(R) gravity

Abstract: In this paper, we work on the topological Lifshitzlike black hole solutions of a special class of vacuum F(R)−gravity that are static and spherically symmetric. We investigate geometric and thermodynamic properties of the solutions with due respect to the validity of the first law of thermodynamics. We examine the van der Waals like behavior for asymptotically AdS solutions with spherical horizon by studying the P − v, G − T and C Q,P − r + diagrams and find a consistent result. We also investigate the same be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 75 publications
(84 reference statements)
1
9
0
Order By: Relevance
“…The roots of the metric function V (r) = g rr = 0 specify the number of horizons, and, as reported in Refs. [32,55,64], the metric function V (r) could have more than two roots. So the multi-horizon black hole solutions are found in massive gravity and we assume that r + is the event horizon radius of the black hole solutions, i.e., the largest real positive root of V (r) = 0.…”
Section: )mentioning
confidence: 99%
See 3 more Smart Citations
“…The roots of the metric function V (r) = g rr = 0 specify the number of horizons, and, as reported in Refs. [32,55,64], the metric function V (r) could have more than two roots. So the multi-horizon black hole solutions are found in massive gravity and we assume that r + is the event horizon radius of the black hole solutions, i.e., the largest real positive root of V (r) = 0.…”
Section: )mentioning
confidence: 99%
“…where the specific volume v is proportional to r + as v = 4r + ℓ d2 P /d 2 [5,10,27,29,30,32]. So, because of the dependency between r + , v and the thermodynamic volume V , criticality in one of P − r + , P − v or P − V planes indicates criticality in the others.…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations
“…gravity. In view of this, various investigations have been discussed with respected to the thermodynamics in the f (R) spacetimes [48][49][50][51]. In these studies, they found that the laws of thermodynamics of f (R) black hole was true.…”
Section: Introductionmentioning
confidence: 99%